2006
DOI: 10.1002/rob.20108
|View full text |Cite
|
Sign up to set email alerts
|

A cooperative perception system for multiple UAVs: Application to automatic detection of forest fires

Abstract: This paper presents a cooperative perception system for multiple heterogeneous unmanned aerial vehicles (UAVs). It considers different kind of sensors: infrared and visual cameras and fire detectors. The system is based on a set of multipurpose low‐level image‐processing functions including segmentation, stabilization of sequences of images, and geo‐referencing, and it also involves data fusion algorithms for cooperative perception. It has been tested in field experiments that pursued autonomous multi‐UAV coop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
123
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 257 publications
(128 citation statements)
references
References 21 publications
0
123
0
5
Order By: Relevance
“…Intellectualization AI is a key technology for future UAV systems to improve their autonomous performance. Intellectualization of UAVs is occurring mainly in terms of autonomous flight path planning ability (Rathbun et al, 2002;Tisdale et al, 2009), autonomous decision-making ability for tasks (Ren et al, 2010), and autonomous air fleet collaboration ability (Merino et al, 2006;Maza et al, 2010). Among these abilities, autonomous path planning is the first intelligent trend in UAVs.…”
Section: Trends In Unmanned Aerial Vehicle Developmentmentioning
confidence: 99%
“…Intellectualization AI is a key technology for future UAV systems to improve their autonomous performance. Intellectualization of UAVs is occurring mainly in terms of autonomous flight path planning ability (Rathbun et al, 2002;Tisdale et al, 2009), autonomous decision-making ability for tasks (Ren et al, 2010), and autonomous air fleet collaboration ability (Merino et al, 2006;Maza et al, 2010). Among these abilities, autonomous path planning is the first intelligent trend in UAVs.…”
Section: Trends In Unmanned Aerial Vehicle Developmentmentioning
confidence: 99%
“…Hollinger et al [108] demonstrated on a single AUV in the Southern California Bight a probabilistic planner that uses uncertainty in ocean current prediction based on an interpolation variance. Merino et al [109] presented a cooperative perception system for multiple UAVs with different kinds of sensors and showed experimental results of forest fire detection with cooperating UAVs. Alvarez et al [110] described methodology that estimates volumetric distribution of the geostrophic current field from glider measurements merged with satellite altimetry data; this methodology was validated using data collected from three Slocum gliders and one Spray glider moving along predefined paths during a field experiment in August 2010 in a coastal region of the Ligurian Sea.…”
Section: Recent Developments and Future Directionsmentioning
confidence: 99%
“…This work contrasts with more traditional work on unmanned aerial vehicle (UAV) coordination where a number of (usually fixed wing) air vehicles are used to search a larger (non urban) area for specific threats such as fires (Merino et al, 2006). Fixed wing UAVs require some care in reconciling the limits of their Dubin paths, with the need to automatically track specific targets, and path optimisation based on Bayesian methods or mutual information has proved to be successful in these instances (Cole et al, 2009;How et al, 2009).…”
Section: Introductionmentioning
confidence: 99%